2003
DOI: 10.1128/jb.185.19.5847-5853.2003
|View full text |Cite
|
Sign up to set email alerts
|

The Naphthalene Catabolic ( nag ) Genes of Ralstonia sp. Strain U2 Are an Operon That Is Regulated by NagR, a LysR-Type Transcriptional Regulator

Abstract: In Ralstonia sp. strain U2, the nag catabolic genes, which encode the enzymes for the pathway that catabolizes naphthalene via the alternative ring cleavage gentisate pathway, are transcribed as an operon under the same promoter. nagR, which encodes a LysR-type transcriptional regulator, is divergently transcribed compared to the nag catabolic genes. A 4-bp frameshift deletion in nagR demonstrated that NagR is required for expression of the nag operon. The transcriptional start of the nag operon was mapped, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 26 publications
4
48
0
Order By: Relevance
“…In many cases, RHO oxygenases have not been identified together with ETC components, thus it has been a challenging task to find a cognate ETC partner that can function in cooperation with these "incomplete" oxygenase components [9,[35][36][37][38][39]. Since some ETCs are interchangeable with each other and can be often replaced by outside ETC sources and it is the terminal oxygenase component that has the catalytic active site, less emphasis was given to ETC components in Nam's classification.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, RHO oxygenases have not been identified together with ETC components, thus it has been a challenging task to find a cognate ETC partner that can function in cooperation with these "incomplete" oxygenase components [9,[35][36][37][38][39]. Since some ETCs are interchangeable with each other and can be often replaced by outside ETC sources and it is the terminal oxygenase component that has the catalytic active site, less emphasis was given to ETC components in Nam's classification.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence comparisons revealed that the regulators in strains JS42 and JS765 (NtdR and NbzR, which are identical in sequence) differ from the regulator in strain U2 (NagR) by only five amino acids. The LysR binding sites and promoters are identical in all three strains, and both regulators activate gene expression in the presence of salicylate, which is an intermediate of the naphthalene degradation pathway and the natural inducer of the naphthalene degradation genes in strain U2 (87,112). However, neither naphthalene nor salicylate serves as a growth substrate for Comamonas sp.…”
Section: Evolutionary Origins Of the Oxidative Pathways For Nitrobenzmentioning
confidence: 99%
“…strain U2, the product of a divergently transcribed lysR-type regulatory gene located upstream of each dioxygenase operon (Fig. 19) activates gene expression in response to recognized inducer compounds (87,89,112). Sequence comparisons revealed that the regulators in strains JS42 and JS765 (NtdR and NbzR, which are identical in sequence) differ from the regulator in strain U2 (NagR) by only five amino acids.…”
Section: Evolutionary Origins Of the Oxidative Pathways For Nitrobenzmentioning
confidence: 99%
See 1 more Smart Citation
“…Because LysR-type regulatory genes associated with naphthalene catabolism are known to be induced by salicylate (Jones et al, 2003) and the promoter of the third catabolic gene cluster was identical to that of the first gene cluster (see above and Supplementary Fig. S2), real-time RT-PCR analysis was conducted to investigate whether the transcription of the third gene cluster was controlled by the nagR regulator of the first gene cluster.…”
Section: Confirming the Regulatory Control Of Nagr On The Third Catabmentioning
confidence: 99%